Overview of the Publication Policies of Major Publishers in Europe and the USA Related to the Use of AI Technology - Hristova, Marieta (Research Papers, 2024)
The objective of this paper is to review existing editorial, publishing, and publication policies in the field of academic publishing powered by AI technologies as part of publishing ethics. The research question is to clarify the publishing industry's response to this challenge. The object of research is the use of AI-assisted technologies and especially ChatGPT in the process of publishing and creating academic texts. The object of the study is the publisher's policy towards the use of AI-assisted technologies. In summary, the main question discussed as to whether a chatbot or an AI-assisted technology can (co-)author a publication is answered negatively, as a chatbot cannot meet the authorship criteria because it cannot be responsible for the content and credibility of the text it creates
Keywords: Ai-assisted technologies; Chatbot; Publishing process; Chat GPT